Accompaniment Application of the Talaqqi Method for Increase Ability Reading the Qur’an, Ladies of the Assembly Ta'lim Pandai Sikek - Sri Wahyuni; Fatimah Harfitriani; Annisa Aulia; Annisa Harianja; Auliana Muslimah; Humaidah Farisa Aina Nuha Lubis; Khosyanti Salsabila Hasibuan (ASSUNNAH PRESS, 2024)
The